Sub-millimetre non-contaminated detection of the disc around TWA 7 by ALMA. Issue 4 (3rd May 2019) - Bayo, A; Olofsson, J; Matrà, L; Beamín, J C; Gallardo, J; de Gregorio-Monsalvo, I; Booth, M; Zamora, C; Iglesias, D; Henning, Th; Schreiber, M R; Cáceres, C
Abstract: Debris discs can be seen as the leftovers of giant planet formation and the possible nurseries of rocky planets. While M-type stars outnumber more massive stars we know very little about the time evolution of their circumstellar discs at ages older than ∼10 Myr. Sub-millimetre observations are best to provide first order estimates of the available mass reservoir and thus better constrain the evolution of such discs. Here, we present ALMA Cycle 3 Band 7 observations of the debris disc around the M2 star TWA 7, which had been postulated to harbour two spatially separated dust belts, based on unresolved far-infrared and sub-millimetre data. We show that most of the emission at wavelengths longer than ∼300 μm is in fact arising from a contaminant source, most likely a sub-mm galaxy, located at about 6.6 arcsec east of TWA 7 (in 2016). Fortunately, the high resolution of our ALMA data allows us to disentangle the contaminant emission from that of the disc and report a significant detection of the disc in the sub-millimetre for the first time with a flux density of 2.1 ± 0.4 mJy at 870 $\rm{μ\, m}$ . With this detection, we show that the spectral energy distribution can be reproduced with a single dust belt.